DEVELOPMENT OF A NOVEL MINERAL BASED HAEMOSTATIC AGENT CONSISTING OF A COMBINATION OF BENTONITE AND ZEOLITE MINERALS - Mortazavi, SMJ; Atefi, M; Shomal, Roshan; Raadpey, N; Mortazavi, G (Journal of Ayub Medical College Abbottabad, 2009)
Background: Haemorrhage remains the greatest threat to life on the battlefield, accounting for half of all deaths. Over the past decade the US army has widely studied new technologies for stopping sever haemorrhages and has introduced an effective zeolite based haemostatic agent. In this paper the bio-stimulatory effect of burned radioactive lantern mantles powder as well as two minerals; bentonite and zeolite are presented. Methods: In this experimental study, 50 male Wistar rats were divided randomly into 5 groups of 10 animals each. Following anaesthesia, animals’ tails were cut off at a thickness of 5 mm by using a pair of surgical scissors. No intervention was made on the animals of the 1st group. The 2nd to 5th group received topical nonradioactive lantern mantle powder, radioactive lantern mantle powder, Bentonite mineral or a mixture of bentonite-zeolite minerals respectively. After treatment with above mentioned agents, the volume of blood loss was measured using a scaled test-tube. The bleeding time (BT) and clotting time (CT) were also measured using a chronometer. Analysis of variance (ANOVA) was used for comparing the means of each parameter in the 5 groups. Results: The volume of blood loss, bleeding and clotting time in control animals were 4.39±1.92 ml, 112.10±39.60 sec and 94.9±54.26 sec respectively. In the 2nd group, in which the animals were treated with a nonradioactive lantern mantle, the volume of blood loss, bleeding and clotting time were 2.34±0.35 ml, 54.50±14.77 sec and 22.9±6.54 sec, respectively. In the 3rd group, in which the animals were treated with a radioactive lantern mantle, the volume of blood loss, bleeding and clotting time were 1.50±0.58 ml, 37.10±7.81 sec and 33.5±15.76 sec respectively. In the 4th group, in which the animals were treated with bentonite mineral, the volume of blood loss, bleeding and clotting time were 1.81±0.62 ml, 55.70±16.73 sec and 45.9±32.17 sec, respectively. In the 5th group, in which the animals were treated with a mixture of bentonite-zeolite minerals, the volume of blood loss, bleeding and clotting time were 1.31±0.60 ml, 34.50±4.65 sec and 24.2±4.61 sec, respectively. Conclusion: To our knowledge, this is the 1st study to investigate the alterations of bleeding and clotting time following the use of lantern mantle powder as well as bentonite or the mixture of bentonite-zeolite minerals. The results obtained in this study clearly show the significant alterations in the volume of blood loss as well as the bleeding or clotting time following the topical use of the mixture of bentonite-zeolite minerals. Controlling the generation of heat was a great achievement in development of the novel haemostatic agent produced in this study. Keywords: Bleeding Time, Clotting Time, Radioactive Lantern Mantle, Minerals, Bentonite, Zeolite